Creating electronic resources for African languages through digitisation: a technical report (Journal of the Digital Humanities Association of Southern Africa, 2023)
The need for electronic resources for (under-resourced) African languages is an often stated one. These resources are needed for language research in general, and more specifically for the development of Human Language Technology (HLT) applications such as machine translation, speech recognition, electronic dictionaries, spelling and grammar checkers, and optical character recognition. These technologies rely on large quantities of high-quality electronic data. Digitisation is one of the strategies that can be used to collect such data. For the purpose of this paper, digitisation is understood as the conversion of analogue text, audio and video data into digital form, as well as the provision of born digital data that is currently not available in a format that enables downstream processing. There is a general perception that the African languages are under-resourced with regard to sufficient digitisation tools to function effectively in the modern digital world. Our paper is presented as a technical report, detailing the tools, procedures, best practices and standards that are utilised by the UP digitisation node to digitise text, audio and audio-visual material for the African languages. The digitisation effort is part of the South African Digital Languages Resources (SADiLaR) project (https://www.sadilar.org/index.php/en/), funded by the Department of Science and Innovation. Our report is based on a best practices document, developed through the course of our digitisation project and forms part of the deliverables as per contractual agreement between the UP digitisation node and the SADiLaR Hub. The workflow as explained in this document was designed with this specific project in mind; software and hardware utilised were also selected based on the constraints with regard to capacity and available technical skills in mind. We motivate our choice of Optical Character Recognition (OCR) software by referring to an earlier experiment in which we evaluated three commercially available OCR programmes. We did not attempt a full-scale evaluation of all available OCR software, but rather focused on selecting one that renders high quality outputs. We also reflect on one of the challenges specific to our project, i.e. copyright clearance. This is particularly relevant with regard to published material. In the absence of newspapers for specifically the African Languages (isiZulu being a notable exception), the biggest portion of textual material available for digitisation consists of printed material such as textbooks, novels, dramas, short stories and other literary genres. The digitisation process is driven by the availability of material for the different languages. Furthermore, obtaining copyright clearance from publishers is a prerequisite for digitisation and especially for the release of any digitised text data for further use and/or processing. Having information on a relatively small-scale digitisation workflow and best practices readily available will enable other interested parties to participate in the digitisation effort, thus contributing to the collection of electronic data for the African languages.
Keywords: digitisation; Optical Character Recognition; copyright; metadata; electronic resources for African Languages